Skeleton model-based approach to integrated engineering design and analysis. Issue 5 (July 2016) - He, Bin; Zhang, Pengchang; Zhu, Ningfeng; Cao, Jintao; Huang, Shan; Tang, Wen
Abstract As concerning the present gap in the dynamic information association and integration between engineering design and engineering analysis, this paper is devoted to a parametric skeleton model-based dynamic information association and integration between design model and analysis model. After the description of the gap between engineering design and analysis was analysed, the modeling method of the product skeleton model was proposed. Then the integrated design and analysis method based on the skeleton model was proposed based on the parameterized design method for analysis. The parametric skeleton model-based design modeling method could be used to resolve the integrating design and analysis problem in product design. The integrated design and analysis of an offshore crane were given as an example with about 25 % time reduction in design cycle, which demonstrates that the methodology is helpful to the associativity of design-analysis models.